Synthesis of AgBr/AgSiOx based photocatalyst by grinding-washing method for organic pollutant degradation under visible light irradiation. (January 2022) - Suwanboon, Sumetha; Randorn, Chamnan; Leesakul, Nararak; Saithong, Saowanit; Kaowphong, Sulawan; Amornpitoksuk, Pongsaton
Abstract: Traditional preparation of photocatalysts via wet-chemical route is considered as energy and solvent-consumable and difficult to scale-up. Herein, a facile method to prepare AgBr/AgSiOx based photocatalysts was developed by grinding AgNO3 with different ratios of NaBr:Na2 SiO3 ·9H2 O. The resulting products contained NaNO3 as an impurity that was removed by washing with a small amount of water. The obtained composites were characterized by X-ray diffractometry, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and UV–vis diffuse reflectance spectroscopy. The photocatalytic properties of AgBr/AgSiOx were evaluated through the degradation of rhodamine B, reactive orange 16, and bisphenol A as pollutant models under visible light irradiation. Photocatalytic activity of AgBr/AgSiOx was higher than those of pure AgSiOx and pure AgBr because the composite was type II heterostructure producing charge separation. Results of trapping experiments showed that the superoxide anion radical and hole were the predominant reactive species during the photocatalytic process and the degradation of the three pollutant models was confirmed by electrospray ionization mass spectrometry. This work offers a simple route to prepare high-efficient photocatalysts for high performance wastewater treatment applications.